2017
DOI: 10.17352/alo.000006
|View full text |Cite
|
Sign up to set email alerts
|

Using the Amphipod Hyale Nigra to Assess the Quality of Marine Sediments

Abstract: Few species are standardized and have been used as test organisms around the world in ecotoxicological assays. In the case of sediment assessment, there are only two amphipod species (Tiburonella viscana and Grandidierella bonnieroides) standardized protocols for toxicity test in South Atlantic region.In order to evaluate the possibility of using the epibenthic marine amphipod Hyale nigra in toxicity tests, a sensitivity test using spiked sediment method was applied, with cadmium chloride as a reference toxica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This study sought to assess the sensitivity of two Brazilian's epibenthic marine amphipods (Hyalenigra and Hyaleyoungi) to reference contaminants in order todetermine their potential as test-organisms in toxicity tests. Passarelli et al (2016) reported the potential of sensitivity of the Brazilian amphipod Hyalenigrato be used as test organisms in sediment toxicity tests and another study showed the sensitivity of Hyaleyoungito enrichment of CO 2 in seawater (Goulding et al 2017). However, this is the first attempt evaluating the sensitivity of these species to toxic substances in water that is useful as reference assay, and considering the environmental parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This study sought to assess the sensitivity of two Brazilian's epibenthic marine amphipods (Hyalenigra and Hyaleyoungi) to reference contaminants in order todetermine their potential as test-organisms in toxicity tests. Passarelli et al (2016) reported the potential of sensitivity of the Brazilian amphipod Hyalenigrato be used as test organisms in sediment toxicity tests and another study showed the sensitivity of Hyaleyoungito enrichment of CO 2 in seawater (Goulding et al 2017). However, this is the first attempt evaluating the sensitivity of these species to toxic substances in water that is useful as reference assay, and considering the environmental parameters.…”
Section: Introductionmentioning
confidence: 99%